Over current protection relay using pic micro controller - Zoolnasri, Abu Harun (2007)
Electrical Power System protection is required for protection of both user and the system equipment itself from fault,hence electrical power system is not allowed to operate without any protection devices installed. Power System fault is defined as undesirable condition that occurs in the power system.These undesirable conditions such as short circuit, current leakage, ground short, over current and over voltage.